Study on enhancement of aerobic granular sludge granulation and its efficiency in white wine brewing wastewater - NING Xinqiang; HU Jialun; PENG Jinmei; HUANG Yuanming; PENG Wei; TANG Tang; ZHENG Jia; LUO Huibo (Gongye shui chuli)
Huang shui fluid(R1) and steamer bottom water(R2) were used as carbon sources, and sodium glucose acetate(R3) was used as a control to investigate the effect of white wine brewing wastewater as a carbon source on the granulation process of aerobic granular sludge. The results showed that the emergence time of particles and particle size were 10 d and 2-3 mm for R1 and 7 d and 3-4 mm for R2,respectively, which were better than 20 d and 0.4-0.6 mm for R3. In terms of sludge concentration and settleability, R1 and R2 were better than R3, where the sludge concentration was 5 413, 5 217 and 2 614 mg/L, and the sludge settling index were 40.85, 39.66 and 53.56 mL/g, respectively. The operation efficiency of each group showed that the average removal rates of COD, ammonia nitrogen, and total nitrogen in the control group were better than those in the experimental group(p<0.05) due to the macromo